Inovação no uso e aceitação da tecnologia da plataforma E-Notariado pelos cartórios da região norte do Estado do Ceará - Linhares, Thales Cavalcante (My University, 2022)
Technological evolution has gained more and more space in the performance of various professionals in the public and private sector, reaching deeply into the notary offices throughout Brazil with virtual mechanisms through online platforms that facilitate the pact of will and the notary services of in order to improve user satisfaction. The changes faced by notaries in the use of technological tools are a real challenge for Brazilian notaries. Thus, the objective of this research is to analyze the perception of the constructs perception of performance expectation, expectation of effort, social influence and facilitating conditions such as the intention to use technology, especially the e-notary platform created by the provision nº 100 of the CNJ ( National Council of Justice), by the registrars, notaries and employees of the notaries in the North Region of the State of Ceará. Classified as exploratory and descriptive, the research adopted the investigation technique with a survey method in which 43 questionnaires were collected from employees and notaries and registrars in the Northern Region of Ceará. Through data analysis with presentation of statistical results, the results found indicated that there are positive repercussions between the intention to use the technology and the variables performance expectation, effort expectation, social influence and facilitating conditions. When comparing users' perceptions of using the platform, especially the variables performance expectation, effort expectation and social influence, results that obtained a higher degree of statistical classification are also found. Regarding the results found on the variable facilitating conditions, they can still be improved for the use of the platform. In addition, the results showed statistical differences when comparing education levels with facilitating conditions, showing that people with higher education have a higher rate of facilitating conditions. [resumo fornecido pelo autor]
A evolução tecnológica tem ganhado espaço cada vez mais nítido na atuação dos vários profissionais do setor público e privado, chegando profundamente nos tabelionados de notas de todo Brasil com mecanismos virtuais através de plataformas on-line que facilitam o pacto de vontade e os serviços cartorários de forma a aperfeiçoar a satisfação de usuários. As mudanças enfrentadas pelos cartórios na utilização de ferramentas tecnológicas são um verdadeiro desafio aos notários brasileiros. Assim, o objetivo desta pesquisa é analisar a percepção sobre os construtos percepção de expectativa de desempenho, expectativa de esforço, influência social e condições facilitadoras como a intenção de uso da tecnologia, especialmente da plataforma e-notariado criada pelo provimento nº 100 do CNJ (Conselho Nacional de Justiça), pelos registradores, tabeliões e funcionários dos cartórios no âmbito da Região Norte do Estado do Ceará. Classificada como exploratória e descritiva, a pesquisa adotou a técnica de investigação com método survey no qual coletaram-se 43 questionários de funcionários e tabeliões de notas e registradores da Região Norte do Ceará. Através das análises de dados com apresentação dos resultados estatísticos, os resultados encontrados indicaram que existem repercussões positivas entre a intenção de uso da tecnologia e as variáveis expectativa de desempenho, expectativa de esforço, influência social e condições facilitadoras. São também encontrados, ao comparar as percepções dos usuários no uso da plataforma, especialmente as variáveis expectativa de desempenho, expectativa de esforço e influência social, resultados que obtiveram maior grau de classificação estatística. Já no que tange aos resultados encontrados sobre a variável condições facilitadoras ainda podem ser melhoradas para o uso da plataforma. Além disso, os resultados mostraram diferenças estatísticas ao comparar os níveis de escolaridade com as condições facilitadoras, mostrando que pessoas com nível superior apresentam maior índice de condições facilitadoras. [resumo fornecido pelo autor]
Keywords: Cartórios - Ceará; Tecnologia; Notaries - Ceará (Brazil); Technology